Influence of SARS-CoV-2 pandemic on sleep habits in a pediatric population - Completo, Sara; Ribeiro, Andreia Fiúza; Manuel, Ana Rute; Loureiro, Helena Cristina (Sleep Science, 2022)
Objective: Assessment of changes in sleep habits at home in children during COVID-19 lockdown.Methods: Retrospective, transversal study in a pediatric ward of a level II hospital. Questionnaires concerning sleep quality, patterns and its modifications during lockdown were distributed from June to August 2020. Comparison with a control sample from previous study (2019). Statistical analysis on SPSS Statistics23.Results: Two groups were compared: during lockdown (n=36, mean age 9.3 years-old) and before lockdown (n=48, mean age 8.8 years-old). 55.6% stated changes in sleep patterns. There was an increase in sleep hours, specifically in school-aged children (p=0.05) and adolescents (p=0.03), with no impact in global subjective sleep quality. Significative increase in screen hours (p=0.02) and its use after dinner (p=0.04).Discussion: Changes in sleep patterns during lockdown were frequent, alongside a higher use of screens. However, these did not affect the subjective sleep quality nor increased the occurrence of sleep disturbances.
Keywords: COVID-19 Pandemic; SARS-CoV-2; Sleep Habits; Electronic Devices; Lockdown